Phenotypic Diversity of Ethiopian Finger Millet [Eleusine coracana (L.) Gaertn] in Relation to Geographical Regions as an Aid to Germplasm Collection and Conservation Strategy - Bezaweletaw, Kebere; Sripichitt, Prapa; Wongyai, Wasana; Hongtrakul, Vipa (Agriculture and Natural Resources, 2007)
Sixty-four accessions (960 individuals) of landraces collected from five former regions of Ethiopia and Eritrea covering different agro-ecologies were characterized for growth habit, ear shape, grain shape, grain surface, grain color and pericarp persistence. The objective was to study the pattern and phenotypic diversity of some characters in finger millet. The experiment was laid down in a randomized complete block design (RCBD) with three replications. The percentage frequencies of the phenotypic classes of each character were calculated. The Shanon-Weaver diversity index (H’) was used to estimate the magnitude of diversity. One way analysis of variance of the non-normalized H using regions was under taken for individual characters. All the character considered showed marked differences in their distribution and variation. In no cases monomorphic classes were observed. Regional wise, Gojam and Welega revealed the highest diversity (H’=0.84) while Eritrea showed the lowest (H’=0.67). There was an increasing trend of diversity from north to south. Overall characters revealed intermediate to high diversity ranging from 0.60 for pericarp persistence to 0.99 for grain surface. Ear shape (P≤0.01), grain shape (Pd≤0.05) and grain surface (Pd≤0.01) showed different levels of diversity among regions as opposed to growth habit, grain color and pericarp persistence whose variations were attributed to among accessions. The overall mean diversity estimate was high (H’=0.82). Generally, the result revealed the existence of a vast range of diversity in the indigenous finger millet germplasm.